Financial literacy among the young: Evidence and implications for consumer policy - Annamaria Lusardi; Olivia S. Mitchell; Vilsa Curto (Goethe University Frankfurt, Center for Financial Studies (CFS), 2010)
We examined financial literacy among the young using the most recent wave of the 1997 National Longitudinal Survey of Youth. We showed that financial literacy is low; fewer than one-third of young adults possess basic knowledge of interest rates, inflation, and risk diversification. Financial literacy was strongly related to sociodemographic characteristics and family financial sophistication. Specifically, a college-educated male whose parents had stocks and retirement savings was about 45 percentage points more likely to know about risk diversification than a female with less than a high school education whose parents were not wealthy. These findings have implications for consumer policy.
urn:nbn:de:hebis:30-78626
Keywords: D91; 330; Financial Knowledge; Peer Effects; Family Background; Finanzmarkt; Wirtschaftsinformation; Wissen; Bildungsniveau; Jugendliche; Verbraucherpolitik; USA